PENGARUH VARIABEL KOMPENSASI FINANSIAL, VARIABEL KOMPENSASI NONFINANSIAL DAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING TERHADAP VARIABEL KINERJA GURU DI SMP NEGERI 11 MALANG - Bukhori, Mochamad; Palemi, Liwindo (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
The study was conducted in SMP Negeri 11 Malang. This study aims to determine the effect of variable compensation of financial and compensation nonfinancial variable to variable work motivation, work motivation variable to variable performance of teachers, and the effect of variable compensation financial and compensation nonfinancial variable to variable performance of teachers through work motivation. This type of research used in this research is causal research design and methods of research used is quantitative. The population in this research were 43 teachers of SMPN 11 Malang. The total sample of 43 teachers using sampling techniques saturated. This research uses descriptive analysis and statistical analysis were used to determine the elements - elements of financial compensation variable, non-financial variable, the variable of work motivation and teacher performance. The results of this study indicate that the variable compensation of financial and compensation nonfinancial a significant influence on work motivation and performance of teachers, both directly and indirectly.